2015
DOI: 10.1111/inm.12138
|View full text |Cite
|
Sign up to set email alerts
|

The value of purpose built mental health facilities: Use of the Ward Atmosphere Scale to gauge the link between milieu and physical environment

Abstract: This study investigated changes in the 'atmosphere' of an acute adult mental health setting following relocation to a new purpose-built facility. The Ward Atmosphere Scale (WAS) was designed and validated for specific use in hospital-based psychiatric facilities, and measures several dimensions of an environment. In this study, the WAS was administered to consumers and staff at periods before and also after their relocation to a new purpose-built acute adult mental health facility. There were significant impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Previous research has reported significantly different ratings between staff and patients on climate measures (Baumgardt et al, 2019; Berry et al, 2016; Moos, 1974; Nicholls et al, 2015; Southard et al (2012); ; ; ; ; ; ; ; . While the literature is not without inconsistencies, the weight of evidence across settings and measures is that, relative to patients, staff overestimate their own abilities as active agents for therapeutic change and that patients, relative to staff, perceive a greater role for themselves in determining ward climate.…”
Section: Methodsmentioning
confidence: 97%
“…Previous research has reported significantly different ratings between staff and patients on climate measures (Baumgardt et al, 2019; Berry et al, 2016; Moos, 1974; Nicholls et al, 2015; Southard et al (2012); ; ; ; ; ; ; ; . While the literature is not without inconsistencies, the weight of evidence across settings and measures is that, relative to patients, staff overestimate their own abilities as active agents for therapeutic change and that patients, relative to staff, perceive a greater role for themselves in determining ward climate.…”
Section: Methodsmentioning
confidence: 97%
“…According to Tyson et al (2002), changes in the physical care environment can positively affect those within it, both improving staff morale and reducing patient morbidity. Nicholls et al (2015) confirmed that architecture is an important influence on the atmosphere of a health facility for both staff and patients. Improvements in the physical milieu led to patients reporting feeling less controlled by staff in the new facility, while staff perceived greater levels of patient involvement.…”
Section: Introductionmentioning
confidence: 66%
“…Howeverdue to redistribution of social activity, isolated and withdrawn behaviour can still appear in another place [49, 51]. The provision of several functionally distinct social spaces can allow opportunities for activities which replicate family life and social activity in the community [30, 32, 52, 53].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies showed that new environments were beneficial for social interactions, and patients reported greater satisfaction with their environment and received care [4, 20, 21, 29–31]. Two studies showed that relocation led to no difference in perceived social support (functional measure of social interaction) [32, 33]. Shepherd and colleagues compared five long-stay inpatient facilities and 20 community facilities to find out that inpatient facilities were characterised with poorer physical environment and significantly less staff-patient interactions [34].…”
Section: Resultsmentioning
confidence: 99%